Interesting game device used in municipal square - MOU ZIXIAN; HUANG ZUHENG; HUANG FENG (2018)
The invention relates to game devices, in particular to an interesting game device used in the municipal square and aims to provide an interesting game device which is used in the municipal square andis high in ornamental value and novel in structure. In order to realize the technical effects, the interesting game device used in the municipal square is provided and comprises a ship model, a mounting plate, a first motor, a first rotating shaft, a connecting rod, a first bearing seat, a second rotating shaft, a connecting block, an annular slide bar, a slide shaft and extrusion blocks, whereinthe mounting plate is arranged on the right side of the top of the ship model; the first motor and the first bearing seat are arranged at the upper part of the front side surface of the mounting plate; the first motor is arranged below the first bearing seat; an output shaft of the first motor is connected with the first rotating shaft through a coupler. The interesting game device has effects ofhigh ornamental value and